2022
DOI: 10.1111/raq.12680
|View full text |Cite
|
Sign up to set email alerts
|

Fruit processing by‐products in the aquafeed industry: A feasible strategy for aquaculture sustainability

Abstract: The aquaculture sector is steadily growing due to the increasing demand for healthy and cheap animal protein sources. Consequently, the high demand for nutritionally balanced aquafeed increases, but requires sustainable and feasible feed ingredients. However, the high cost of fish and soybean meals opens the door to looking for suitable non‐traditional feed ingredients. The processing of fruits results in high amounts of waste and by‐products, which are risky for the environment but rich in nutritional value. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 127 publications
0
26
0
Order By: Relevance
“…Nevertheless, poor reproductive performance, lack of quality feed, and husbandry requirements are major issues in managing the female stinging catfish broodstock culture. Therefore, aquaculture nutritionists consistently search for novel, high-quality alternatives of plant and animal origin [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, [ 16 , 17 , 18 ] it has been reported manipulating the nutrient composition of broodfish diets improves spawning response, lowers the number of broodfish required to achieve production goals, and enhances egg production and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, poor reproductive performance, lack of quality feed, and husbandry requirements are major issues in managing the female stinging catfish broodstock culture. Therefore, aquaculture nutritionists consistently search for novel, high-quality alternatives of plant and animal origin [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, [ 16 , 17 , 18 ] it has been reported manipulating the nutrient composition of broodfish diets improves spawning response, lowers the number of broodfish required to achieve production goals, and enhances egg production and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit processing wastes and products were estimated to be approximately 100 million tonnes, and management has become challenging for industrial players (Fierascu et al, 2020;Marić et al, 2018). Studies have shown that fruit processing wastes and by-products are promising supplements for aquaculture species due to the presence of bioactive compounds and exogenous enzymes (Dawood et al, 2022;Habotta et al, 2022). For instance, banana peel flour incorporated with fish feed 5% promoted the health of rohu, L. rohita (Giri et al, 2016).…”
Section: Vegetables and Fruits Wastementioning
confidence: 99%
“…yeast, malt sprouts, spent brewers grains) 78–80 . Some ingredients which could be circular source of additives such as spent coffee grains, fruit and vegetable byproduct 73,81 . Besides providing nutrients for downstream ingredient production (e.g.…”
Section: Cbf and Its Relevance In Aquaculture Nutritionmentioning
confidence: 99%